Transformation of Social Responsibility Types in Small Business During COVID-19 Crisis - A. O. Vekshina (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
Year after year social responsibility becomes more popular among companies. Today nearly all companies introduce this concept. In spite of rather long evolution and transformation of this concept in Russia, it should be pointed out that by 2020 social responsibility began spreading among small and medium business, however the crisis had a serious impact on it. A lot of companies started fighting for survival and responsibility to others stepped back. The goal of the research is to study in what way the format and types of social activities changes when corona virus turned up. The article analyzes theoretical approaches to the notion ‘social responsibility’ and provides findings of the survey among representatives of small business trading on marketplaces. The research shows that entrepreneurs shifted their attention to the on-line format and started to distribute their priorities in a different way. The author highlighted the acute trends in conditions of economic crisis in Russia, identified lines in developing social responsibility and also pointed out problems, which have been focused on by entrepreneurs and those, which should be distinguished in the near future.